2013
DOI: 10.1108/jcs-04-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Promising parenting programmes for reducing adolescent problem behaviours

Abstract: Purpose Adolescent problem behaviors (substance use, delinquency, school dropout, pregnancy, and violence) are costly not only for individuals, but for entire communities. Policymakers and practitioners that are interested in preventing these problem behaviors are faced with many programming options. In this review, we discuss two criteria for selecting relevant parenting programs, and provide five examples of such programs. Design/methodology/approach The first criterion for program selection is theory base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 45 publications
1
25
0
1
Order By: Relevance
“…In addition, in bivariate analysis, lack of peer support at school was associated with early sexual debut. Therefore, specific parenting programmes and interventions that strengthen young people's pro-social relationships can be promoted in reducing adolescent problem behaviours (17,18). Moreover, this study found that sedentary behaviour was a risk for early sexual debut.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, in bivariate analysis, lack of peer support at school was associated with early sexual debut. Therefore, specific parenting programmes and interventions that strengthen young people's pro-social relationships can be promoted in reducing adolescent problem behaviours (17,18). Moreover, this study found that sedentary behaviour was a risk for early sexual debut.…”
Section: Discussionmentioning
confidence: 77%
“…Our results suggest ways to approach the identification of at-risk families (e.g., via parenting styles). Parental monitoring—and authoritative parenting more broadly—can be taught (Steinberg, Fletcher, & Darling, 1994), and family-based interventions have shown promise in reducing or preventing substance abuse (Haggerty, McGlynn-Wright, & Klima, 2013). Finally, our results suggest that fathers play an important role in offspring’s propensity to use drugs and should be included in family-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Aun cuando los autores (David Hawkins y Richard Catalano) siempre han considerado que la clave del éxito está en la correcta selección de los programas de prevención en la fase 5 (Haggerty y Shapiro, 2013;Haggerty, McGlynn-Wright y Klima, 2013;Hawkins et al, 2002;Shapiro, Hawkins, Oesterle, Monahan, Brown y Arthur, 2013;Steketee, Oesterle, Jonkman, Hawkins, Haggerty y Aussems, 2013), la experiencia en Colombia muestra que las cuatro primeras fases consolidan procesos en la comunidad que ninguna otra estrategia preventiva ha logrado: solidaridad, toma de conciencia sobre la responsabilidad del futuro de los jóvenes, necesidad de identificar los factores protectores y de riesgo y de modificarlos cada vez que sea posible y necesario, y de evaluar sistemáticamente los comportamientos problemáticos y las formas de afrontarlos. Ésta será la condición necesaria para que la implementación de los planes de acción sea exitosa.…”
Section: Discussionunclassified